Ride-hailing service in Vietnam market and its impacts on travel behavior of local people - Nguyễn, Danh Minh (2020)
Ride-hailing service (RHS) is a new travel mode in urban transport system, it is called as the technology taxi service in Vietnam. Ride-hailing is the act of requesting a ride from a private passenger vehicle by an app on a smartphone. RHS has appeared in Vietnam from 2014, however, it has spread rapidly and affect significantly to Vietnam transport market and travel habit of people. Until now, there has been still no completed regulation for the operation of RHS in Vietnam. RHS has caused big controversy with the domestic taxi industry, traditional taxi companies claim that RHS is no different from taxis, and that ride-hailing companies (RHCs) should be held to the same operating requirements and regulations as taxi companies, including licensing, fare regulation, and vehicle and driver safety standards in order to maintain an equal and fair playing field. The research has also evaluated qualitatively impacts of RHS on local people. The results show that people usually use Grab for picking up/sending off their children. Some people use Grab to replace their private vehicle to go to work or use it as a paratransit mode. After examining the dynamic characteristic of the RHS car, some interesting findings have been revealed. The fluctuation of the price of Grab depends on the demand of the market. When the demand is high, the price of the trip will high and vice versa. The great fluctuation of price frequently happens at the morning peak – hour (6h-9h) on weekdays when people have a high demand for going to work. On the weekend, the price frequently fluctuates widely in the afternoon (16h30-19h), in the evening (19h-22h) and at night (22h-23h) when people have a high demand for leisure purpose and going back their home. The waiting time for a RHS car does not only depend on the number of the available car around but also depends on the distance between the vehicle and the customer. A potential assumption also has been proposed that the algorithm of Grab app automatically raises prices to balance between demand and supply because when bad conditions happen